2014
DOI: 10.4490/algae.2014.29.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate change on the physiology of giant kelp, Macrocystis pyrifera, and grazing by purple urchin, Strongylocentrotus purpuratus

Abstract: As global warming continues over the coming century, marine organisms will experience a warmer, more acidic ocean. Although these stressors may behave antagonistically or synergistically and will impact organisms both directly (i.e., physiologically) and indirectly (i.e., through altered species interactions), few studies have examined the complexities of these effects in combination. To address these uncertainties, we examined the independent and combined effects of elevated temperature and pCO 2 on the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 42 publications
5
45
0
Order By: Relevance
“…Across all years and treatments, we find that M. pyrifera in the Monterey Bay utilize bicarbonate via external catalysis to support an average 40% of PS, corroborating the findings of Brown et al. (). The remaining 60% of photosynthesis is supported by dissolved CO 2 and an unknown proportion of active bicarbonate uptake via ion exchange proteins.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Across all years and treatments, we find that M. pyrifera in the Monterey Bay utilize bicarbonate via external catalysis to support an average 40% of PS, corroborating the findings of Brown et al. (). The remaining 60% of photosynthesis is supported by dissolved CO 2 and an unknown proportion of active bicarbonate uptake via ion exchange proteins.…”
Section: Discussionsupporting
confidence: 89%
“…Recent work has focused on the effects of variable pH environments on carbon acquisition (Brown et al. , Fernández et al. ), but we have little information regarding the effects of variable irradiance and current velocities on carbon uptake dynamics in M. pyrifera .…”
mentioning
confidence: 99%
“…Previous experimental and observational studies have identified that rising temperatures can decrease kelp survival, growth, photosynthesis, spore production, spore germination, recruitment, and harvest yield (Valdez et al 2003, Davoult et al 2011, Harley et al 2012, Wernberg et al 2013, Brown et al 2014). Previous experimental and observational studies have identified that rising temperatures can decrease kelp survival, growth, photosynthesis, spore production, spore germination, recruitment, and harvest yield (Valdez et al 2003, Davoult et al 2011, Harley et al 2012, Wernberg et al 2013, Brown et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental and observational studies have identified that rising temperatures can decrease kelp survival, growth, photosynthesis, spore production, spore germination, recruitment, and harvest yield (Valdez et al 2003, Davoult et al 2011, Harley et al 2012, Wernberg et al 2013, Brown et al 2014). However, these effects were generally observed over temperature ranges that span 2°-20°C over ambient (Fain and Murray 1982, Deysher and Dean 1986, Wernberg et al 2010, Brown et al 2014. Response to such a small increase in temperature as that which was observed in this study may be expected where a species is near its physiological temperature tolerance limit.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we performed the feeding experiments only with the sea urchin P. lividus , whereas different herbivore species may have responded differently to CO 2 -driven changes in plant chemical composition4574 or epiphyte abundance or composition since it is expected that fleshy epiphytes may increase93 and calcareous epibionts would decrease their abundance under low pH conditions30. While we only performed the feeding experiments under ambient CO 2 water conditions, studies to date with adult sea urchins do not suggest strong changes in feeding rates9495, nor in preferences (S.R. Fitzpatrick, personal communication) under ambient vs. high p CO 2 conditions.…”
Section: Discussionmentioning
confidence: 99%